ANALISA KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KLATEN TAHUN 2017 – 2020 - Erwin Budi Setyawan (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to find out how the contribution of local taxes to the local revenue of PAD and the growth of local taxes for the period 2017-202. The location of this research was carried out at the BPKAD office, Klaten Regency, this type of research was descriptive qualitative, and used data analysis techniques using ratio analysis. From this study, the following results were obtained, the contribution of local taxes to local revenue for the period 2017-2020 is quite good with an average of 47%. The largest contribution of local taxes is dominated by street lighting tax, which is 36.4%, and the growth of local taxes and local revenue in 2017-2020 was negatif correlated where the averages were 3.63% and 17.53%.